Clinicopathological features and treatment outcome of paediatric differentiated thyroid cancer treated with Radioactive Iodine-131 therapy in Hospital Kuala Lumpur, Malaysia - Khor, Phay Phay; Suppiah, Subapriya; Wong, Teck Huat; Amir Hassan, Siti Zarina (Malaysian Medical Association, 2021)
Background: Radioactive iodine 131I (RAI) therapy is one of the definitive treatments for paediatric differentiated thyroid cancer (DTC) initiated at nuclear medicine departments. In Malaysia, there is a need to identify the standardisation of treatment regimes to align with international standards. We aimed to evaluate the clinicopathological features and the patient response to RAI therapy among paediatric DTC cases at Hospital Kuala Lumpur (HKL), Malaysia. Methods: A retrospective, longitudinal study was conducted among paediatric DTC patients treated with RAI in HKL and followed up between 2000-2016. Sixty-five patients were studied (mean period: 58.8±36 months). The clinicopathological data of the patients was recorded, and descriptive analysis was made. The association between categorical and continuous data with disease status was assessed using chi-square and Kruskal-Wallis tests, p-value <0.05 taken as statistically significant. Results: Most patients were female (78.5%), and adolescents comprised 89.2%. Pre-pubertal age, those presenting with cervical nodal involvement, extra-thyroidal extension and lymphovascular invasion were significantly associated with distant metastases at presentation. There was no mortality reported during the follow-up period. Sixty per cent of patients achieved remission, while 40% had persistent disease. The persistent disease was significantly correlated with distant metastasis at presentation (p=0.025). Conclusions: Paediatric DTC manifests with a more extensive disease burden at presentation and requires multiple RAI doses. Despite this, it carries an excellent overall prognosis.